Resuscitation therapy for traumatic brain injury-induced coma in rats: mechanisms of median nerve electrical stimulation - Zhen Feng; Ying-jun Zhong; Liang Wang; Tian-qi Wei (Neural Regeneration Research, 2015)
In this study, rats were put into traumatic brain injury-induced coma and treated with median nerve electrical stimulation. We explored the wake-promoting effect, and possible mechanisms, of median nerve electrical stimulation. Electrical stimulation upregulated the expression levels of orexin-A and its receptor OX1R in the rat prefrontal cortex. Orexin-A expression gradually increased with increasing stimulation, while OX1R expression reached a peak at 12 hours and then decreased. In addition, after the OX1R antagonist, SB334867, was injected into the brain of rats after traumatic brain injury, fewer rats were restored to consciousness, and orexin-A and OXIR expression in the prefrontal cortex was downregulated. Our findings indicate that median nerve electrical stimulation induced an up-regulation of orexin-A and OX1R expression in the prefrontal cortex of traumatic brain injury-induced coma rats, which may be a potential mechanism involved in the wake-promoting effects of median nerve electrical stimulation.